Performance Evaluation of Back-End Frameworks: A Comparative Study - Carmo, Klayver Ximenes; Ferreira, Fischer; Figueiredo, Eduardo (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2024)
Context: In today’s technological landscape, the development of Web information systems, especially in the back-end, is an essential and constantly evolving activity. The choice of technology for this layer is crucial to ensuring the performance, security and efficiency of the system as a whole. Problem: To date, recent literature lacks studies that address the identification of specific requirements and characteristics to guide the selection of a back-end technology for Web systems. Solution: This paper carries out a comparative analysis of the most widely used back-end technologies according to the most recent survey by Stack Overflow: Node.js, Django REST Framework (DRF) and ASP.NET Core. IS Theory: This study was developed under the guidance of Performance Evaluation Frameworks, aimed at guiding the choice of back-end technologies in the architecture of Web information systems. Method: To conduct this study, an API server was implemented in each of the technologies to carry out tests and collect data and metrics, such as performance in different scenarios. Summarization of results: The results highlighted that.NET had a high consumption of resources, while Node.js and DRF showed low consumption and similar performance. In terms of response times,.NET was most effective, followed by Node.js and DRF. Contributions and impact on IS: The results of this study benefit developers, companies and researchers by providing information for choosing back-end technologies, as well as serving as a reference point for researchers working in the field.